1990
DOI: 10.1002/1520-6807(199001)27:1<57::aid-pits2310270109>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

A survey of school psychologists' perspectives and practices with childhood depression

Abstract: Despite some controversy, there is an emerging body of knowledge regarding the nature, prevalence, assessment, and treatment of childhood depression. The following study was undertaken to determine how this knowledge compares with the perceptions and practices of school psychologists in two north central states. A need for school psychologists to define the concept of childhood depression is identified. Use of DSM 111-R for the diagnosis of childhood depression in the schools and the inclusion of standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There might appear to be a very direct correspondence between the DSM-IV categories of "depression" and "mood disorder" and the IDEA requirement of "a general pervasive mood of unhappiness or depression. However, there are cases when a DSM-IV diagnosis might be made by a clinician but be unsupported by IDEA when only a student's academic performance and behavior in school has been used to assess eligibility for special services and it is found that the student is coping in the school setting.. Clarizio and Payette (1990) describe a survey of school psychologists that suggests their practice in treating depression relied more on the operational criteria of the Diagnostic and Statistical Manual of Mental Disorders, third edition revised (DSM-III-R) than on IDEA. Other studies that attempted to measure this aspect of the school psychologist's practice with respect to treating other conditions could not be found but the indications from the writer's awareness of school psychology practice and the published work of many school psychologists is that school psychologists do frequently rely on the DSM-IV to make a diagnosis of serious emotional disturbance.…”
Section: Statementioning
confidence: 99%
See 1 more Smart Citation
“…There might appear to be a very direct correspondence between the DSM-IV categories of "depression" and "mood disorder" and the IDEA requirement of "a general pervasive mood of unhappiness or depression. However, there are cases when a DSM-IV diagnosis might be made by a clinician but be unsupported by IDEA when only a student's academic performance and behavior in school has been used to assess eligibility for special services and it is found that the student is coping in the school setting.. Clarizio and Payette (1990) describe a survey of school psychologists that suggests their practice in treating depression relied more on the operational criteria of the Diagnostic and Statistical Manual of Mental Disorders, third edition revised (DSM-III-R) than on IDEA. Other studies that attempted to measure this aspect of the school psychologist's practice with respect to treating other conditions could not be found but the indications from the writer's awareness of school psychology practice and the published work of many school psychologists is that school psychologists do frequently rely on the DSM-IV to make a diagnosis of serious emotional disturbance.…”
Section: Statementioning
confidence: 99%
“…Clarizio and Payette (1990) describe a survey of school psychologists that suggests their practice in treating depression relied more on the operational criteria of the Diagnostic and Statistical Manual of Mental Disorders , third edition revised (DSM-III-R) than on IDEA. Other studies that attempted to measure this aspect of the school psychologist's practice with respect to treating other conditions could not be found but the indications from the writer's awareness of school psychology practice and the published work of many school psychologists is that school psychologists do frequently rely on the DSM-IV to make a diagnosis of serious emotional disturbance.…”
Section: Definition Of Serious Emotional Disturbancementioning
confidence: 99%